Putative interchromosomal rearrangements in the hexaploid wheat (Triticum aestivum L.) genotype 'Chinese Spring' revealed by gene locations on homoeologous chromosomes - Ma, Jian; Stiller, Jiri; Zheng, Zhi; Wei, Yuming; Zheng, You-Liang; Yan, Guijun; Doležel, Jaroslav; Liu, Chunji (BMC evolutionary biology, 2015)
BACKGROUND: Chromosomal rearrangements are a major driving force in shaping genome during evolution. Previous studies show that translocated genes could undergo elevated rates of evolution and recombination frequencies around these genes can be altered. Based on the recently released genome sequences of Triticum urartu, Aegilops tauschii, Brachypodium distachyon and bread wheat, an analysis of interchromosomal translocations in the hexaploid wheat genotype 'Chinese Spring' ('CS') was conducted based on chromosome shotgun sequences from individual chromosome arms of this genotype. RESULTS: A total of 720 genes representing putative interchromosomal rearrangements was identified. They were distributed across the 42 chromosome arms. About 59% of these translocated genes were those involved in the well-characterized translocations involving chromosomes 4A, 5A and 7B. The other 41% of the genes represent a large numbers of putative interchromosomal rearrangements which have not yet been described. The number of the putative translocation events in the D subgenome was about half of those presented in either the A or B subgenomes, which agreed well with that the times of interaction between the A and B subgenomes almost doubled that between either of them and the D subgenome. CONCLUSIONS: The possible existence of a large number of interchromosomal rearrangements detected in this study provide further evidence that caution should be taken when using synteny in ordering sequence contigs or in cloning genes in hexaploid wheat. The identification of these putative translocations in 'CS' also provide a base for a systematic evaluation of their presence or absence in the full spectrum of bread wheat and its close relatives, which could have significant implications in a wide array of fields ranging from studies of systematics and evolution to practical breeding.
Keywords: Chromosome Mapping; Poaceae; Triticum; Chromosomes, Plant; rostlinné geny; syntenie; translokace genetická; pšenice; Genome, Plant; Synteny; genom rostlinný; chromozomy rostlin; lipnicovité; Genes, Plant; mapování chromozomů; Translocation, Genetic